Basin Evolution and Shale Tectonics on an Obliquely Convergent Margin: The Bahia Basin, Offshore Colombian Caribbean. Issue 3 (11th March 2020) - Galindo, Pedro A.; Lonergan, Lidia
Abstract: Oblique convergent margins accumulate strike‐slip deformation that controls basin formation and evolution. The Bahia Basin is located offshore, proximal to major strike‐slip fault systems that affect northern Colombia. It lies behind the toe of the modern accretionary prism, where the Caribbean Plate is being subducted obliquely beneath South America. This is the first attempt using 3‐D seismic reflection data to interpret a complex strike‐slip basin at the western end of the southern margin of the Caribbean Plate. Detailed 2‐D and 3‐D seismic mapping of regional unconformities and faults is used to describe the structural geometry, timing, and evolution of extensional and strike‐slip faults, which controlled the formation of the basin. Analysis of the fault zones is coupled with a description of the seismic‐stratigraphic units observed within the Bahia Basin to reconstruct the spatial and temporal evolution of deformation and to evaluate the influence of the pervasive shale tectonics observed in the area. The results, presented as a series of structural‐paleogeographic maps, illustrate an initial stage of transtension that controlled the formation of shale‐withdrawal minibasins from late Oligocene to late Miocene times. The continuous deformation and northward expulsion of the Santa Marta Massif resulted in transpression during Pliocene times, leading to basin inversion and ultimate closure of the basin. Basin evolution along the southern Caribbean oblique, convergent margin, shows the occurrence of a complex interaction between subduction and major‐onshore strike‐slip fault systems and illustrates how strain‐partitioning led to the break‐up and lateral displacement of early accretionary prisms formed along the margin. Key Points: In response to oblique convergence, strike‐slip deformation occurs at the rear of the South Caribbean Deformed Belt and controls the evolution of the Bahia Basin Strike‐slip deformation and sediment loading triggered the movement of overpressured shale, creating mud‐withdrawal minibasins Strain‐partitioning led to the break‐up and lateral displacement of accretionary prisms formed along the margin, opening the space for depocenters